A study of HER-2/neu expression and silver binding nucleolar organizer regions (Ag NORs) in perilesional normal salivary gland tissue - Essam Taher M.A. Gaballah (Elsevier, 2010)
Salivary gland neoplasms comprise phenotypically and biologically diverse lesions of uncertain histogenesis. Objectives: The present study was carried out to assess the immunohistochemical expression of HER-2/neu protein and of silver binding nucleolar organizer regions in normal salivary tissue. Materials and methods: Twenty paraffin blocks of salivary tumors containing surrounding normal salivary tissue were used in the study. One section was processed to investigate HER-2/neu protein expression and another section was stained to assess the mean Ag NOR counts in normal salivary tissue. Results: Only two cases of the studied normal salivary tissue showed HER-2/neu expression (10%), which was expressed only in ductal cells with 4.2 ± 2.1 mean number of reactive cells per five high power fields (HPFs). Statistically significant (P = 0.01) higher mean Ag NOR counts in ductal (2 ± 0.83) than in acinar cells (1.2 ± 0.01) of normal salivary tissue were found. Conclusion: It was concluded from the data of the present study that ductal cells of normal salivary tissue are a proliferative pool and an oncogenic target which plays an important role in the histogenesis of salivary gland tumors. Keywords: Histogenesis, HER-2/neu expression, AgNORs, Salivary gland neoplasms